Mental health awareness among students of IIUM - Abdul Razak, Mohd Abbas (2017)
Due to the phenomenal increase in issues related to mental illness in Malaysia and elsewhere in the world, this presentation appeals to the students of IIUM to pay a serious attention to their state of mental health. It has come to the knowledge of the presenters during their counselling sessions with students who go through stress, anxiety, and other mild psychopathological symptoms, that most students are not aware of the importance of maintaining a good balance in their bodily, psychological and spiritual needs. The ultimate aim of this presentation is to bring to the awareness of the students that in their pursuit of academic excellence they should not undermine the importance of enjoying a good level of mental health. It is the contention of the presenters that spirituality plays a vital role in averting all forms of mental illness.